Adinandra sadaui - Tanggaraju, S.; Tsen, S.; Damit, A.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Adinandra sadaui is restricted to Ranau. The estimated area of occupancy (AOO) and extent of occupancy (EOO) are both 4 km2. Due to land use change there is continuing decline inferred in area of habitat. The species is located in Tagudon Paginatan road which is an open area, possibly by degraded road reserve. This species has not been collected since 1965. Hence, it is assessed as Critically Endangered. Adinandra sadaui is endemic to Borneo, Sabah, Malaysia. It is restricted to the Ranau area of Togudon Paginatan Road. The species has not been collected since 1965 and therefore additional survey is needed to confirm the species is still present in this locality or the local vicinity.